Kajian Penataan Lahan Pasca Tambang Diorit CV. Mineral Cahaya Bumi Kecamatan Sungai Kunyit Kabupaten Mempawah Provinsi Kalimantan Barat - Leonardus IP Deo; Fitriana Meilasari; Budhi Purwoko; hendri sutrisno (Jurnal Teknologi Lingkungan Lahan Basah, 2022)
Diorite mining activities have the potential to cause environmental degradation. Therefore, there is a need for reclamation. Reclamation is part of environmental control in implementing Good Mining and Operational Practice. One of the stages in the implementation of reclamation is the arrangement of post-mining land. The soil arrangement system is divided into 3 (three) systems, namely the soil leveling system, the guludan system, and the pot system. Land management system based on top soil needs. Therefore, this research aims to analyze the land management system and determine the optimal topsoil stocking system. The method used in this research is a qualitative method of analysis. Data processing uses AutoCAD 2021 software and ArcGis 10.8 software. The cross-sectional method is used in data processing to determine the availability of topsoil and topsoil in the study area. The results obtained in this study are (1) The planned area of the reclamation area is ± 5.29 hectares; (2) The overburden stocking volume is 35,397.56 LCM; (3) The volume of distribution of topsoil using the land leveling method is 13,387.96 LCM.